Analysis of the productive performance and physical-mechanical characteristics of Nile tilapia leathers fed with different levels of propolis in the rations (Research, Society and Development, 2021)
The objective of this work was to evaluate the productive performance and physical-mechanical parameters of Nile tilapia leather, influenced by the inclusion of SL491* (based on propolis) in the rations. An experiment was conducted with six treatments (0, 50, 100, 150, 200 and 250 g of SL491* / 100 kg of feed) and four replications, the experimental unit being composed of a 500 L box containing four fish (weight initial 13 g). After 160 days, the fish were weighed and measured to analyze their productive performance, and processed until the skins were removed, which were subjected to tanning. The physical-chemical parameters of the water did not differ between treatments, in relation to productive performance, the addition of SL491* promoted a positive effect on fish weight, on average weight gain, however it did not interfere with feed conversion. The fillet yield, raw skin and clean skin without scales were not influenced by the addition of SL491*. When the parameters of the quality of the hides were evaluated, the thickness, the maximum force applied in the test and the progressive tearing increased with the addition of the SL491* product based on propolis in the ration. There was no influence of the addition of SL491* in the ration regarding the parameters of maximum applied force in determining traction and elongation, for elasticity (elongation), for tensile strength and specific deformation until leather rupture. It is concluded that the inclusion of up to 200g of SL491*/100kg of feed promotes a positive effect on the performance of tilapia and on the final quality of the hides.